2016
DOI: 10.1002/2016jd025218
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal transition of precipitation characteristics associated with land surface conditions in and around Bangladesh

Abstract: This study examined the seasonal transition of precipitation characteristics and its association with land surface conditions in and around Bangladesh, where land surface conditions are predominantly wet. Hourly rain rate data from the Global Satellite Mapping of Precipitation Microwave‐Infrared Combined Product and 10 day soil moisture data from the Advanced Microwave Scanning Radiometer Earth Observing System were used over the 7 years from 2003 to 2009. Area mean values of soil moisture, and precipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Although many numerical studies have shown the simulated evidence, it is generally difficult to obtain observational evidence. For example, Ono and Takahashi (2016) and Takahashi (2016) showed a similar tendency of the effect of land-surface conditions on rainfall intensity over the wet Asian monsoon region from observed datasets. However, more studies are required to fully understand the mechanisms of these responses.…”
Section: Introductionsupporting
confidence: 57%
“…Although many numerical studies have shown the simulated evidence, it is generally difficult to obtain observational evidence. For example, Ono and Takahashi (2016) and Takahashi (2016) showed a similar tendency of the effect of land-surface conditions on rainfall intensity over the wet Asian monsoon region from observed datasets. However, more studies are required to fully understand the mechanisms of these responses.…”
Section: Introductionsupporting
confidence: 57%
“…We also found positive correlation during pre‐monsoon ( r = 0.663) than monsoon ( r = 0.455). Relatively low correlation in this study may be attributed to a variety of factors such as mesoscale convective system of the region (Choudhury et al ., ), seasonal transition of precipitation characteristics (Ono and Takahashi, ), cloud height, intensity of rainfall, ice content per lightning flash and properties of precipitation systems (Islam and Uyeda, ; Lal and Pawar, ; Rafiuddin et al ., ). Rafiuddin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 and 2 of the MJO circulation creates a strong moisture convergence near the Meghalaya Plateau, leading to intensified precipitation over northeast India and the northern Bangladesh region during the summer monsoon. Several studies have also reported that changes in soil moisture contribute to the pre‐monsoon and monsoon precipitation variation over Bangladesh (Ono and Takahashi, 2016; Sugimoto and Takahashi, 2017).…”
Section: Introductionmentioning
confidence: 99%